2021
DOI: 10.15407/agrisp8.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulatory activity in the phytopathogenic fungus Plectosphaerella melonis strain 502

Abstract: Aim. To investigate the ability of our phytopathogenic fungal strain 502, earlier preliminarily identified as the phytopathogen Plectosphaerella melonis (syn. Acremonium cucurbitacearum), to have phytotoxic and/or plant growth regulatory activity. Methods. The phytotoxicity of strain 502, was studied by bioassays using the test cultures of corn (Zea mays L.), garden cress (Lepidium sativum L.), cucumber (Cucumis sativus L.), and onion (Allium cepa L.). The cytotoxicity and genotoxicity of the fungus were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The improvement in the growth and development of these plants may be conditioned by the synthesis of growth-regulating compounds, stimulating the ontogenesis processes in the initial stages of mycelium growth in plant tissues, but further development of the fungus in the host plant tissues is accompanied by the excess of phytohormones. Previously we have shown that P. melonis strain 502 synthesizes the ethylene phytohormone in vitro, and the cultural liquid of P. melonis strain 502 is characterized by growth-regulating properties and may inhibit or stimulate the growth of plants depending on the dilution and the test plant (Tsekhmister et al, 2021). It is generally known that many plant pathogens pretend to be mutualistic, and at fi rst, they stimulate the growth of a host plant; artifi cially infected plants look greener and healthy, then there are manifestations of the damage and even collapse of plants (van Baalen and Jansen, 2001;Bronstein, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement in the growth and development of these plants may be conditioned by the synthesis of growth-regulating compounds, stimulating the ontogenesis processes in the initial stages of mycelium growth in plant tissues, but further development of the fungus in the host plant tissues is accompanied by the excess of phytohormones. Previously we have shown that P. melonis strain 502 synthesizes the ethylene phytohormone in vitro, and the cultural liquid of P. melonis strain 502 is characterized by growth-regulating properties and may inhibit or stimulate the growth of plants depending on the dilution and the test plant (Tsekhmister et al, 2021). It is generally known that many plant pathogens pretend to be mutualistic, and at fi rst, they stimulate the growth of a host plant; artifi cially infected plants look greener and healthy, then there are manifestations of the damage and even collapse of plants (van Baalen and Jansen, 2001;Bronstein, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Strain. A natural strain of fungus P. melonis strain 502, isolated from the diseased roots of cucumber plants (C. sativus cv Koroliok), cultivated in the covered soil, was used in the work (Kopilov et al, 2021;Tsekhmister et al, 2021). The strain was deposited in the Depository of the Institute of Microbiology and Virology, NAS of Ukraine, and numbered IMV F-100138.…”
Section: мAterials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation